Giveaways and Gifts with Caliph Othman bin Affan, may God be pleased with him - Abdullah , Saad (Islamic Sciences Journal, 2023)
ABSTRACT This study talks about the gifts and donations that were distributed by Caliph Othman bin Affan, may God be pleased with him, as he was one of the owners of money and was always donating them to Muslims as individuals in particular and to the state in general The funds that Caliph Othman used to distribute varied between cash and in-kind money. He also sometimes distributed lands, and these donations, especially during the days of his caliphate, contributed to the first half of them in improving the economic conditions of Muslims, especially his relatives, who gave them a lot of money as a matter of kinship, as well as given to the rest of the Muslims in order to bring them closer and earn them alongside the caliphate However, at the same time, these donations were another weapon, When they aroused the resentment of many people against Othman, under the pretext that he was disposing of Muslim money for his relatives. This accusation proved invalid as he used to donate his own money to his relatives .This did not prevent him from giving money to the rest of the Muslims, so he was fair and keen on people money and more generous in the distribution of his own money. As a result of the abundance of money, new and tyrannical customs appeared on the Islamic community, so he fought them and stood against them.